INTEGRASI SAINS DALAM MATERI PEMBELAJARAN BAHASA ARAB PADA PERGURUAN TINGGI KEAGAMAAN ISLAM - Imelda Wahyuni (Zawiyah: Jurnal Pemikiran Islam, 2016)
This paper discusses the integration of science in the preparation of learning materials in Arabic on Islamic Higher Education in Indonesia. Arabic learning is inseparable from the study of linguistics, particularly in understanding some of the terms related to the meaning attributed to the word "language". Meanings of the word strongly associated with language learning objectives, so that the language can be interpreted as a science and as a communication tool. This study also illustrates some characteristics of language that could be enlightening understanding of the learners about the language in general, such understanding is expected to be synergized with learning materials one foreign language at the Islamic Higher Education, namely Arabic. Arabic material design should be based on facts, concepts, principles, and skills. The fact is the socio-cultural reality of the academic environment and the needs of disciplines based on each department. The use of conceptual studies in the preparation of the material helps theoretical representation regarding the material in Arabic. The principle in the preparation of materials in line with the principle of learning Arabic, which is the principle of priority, gradation, and motivation. Preparation of Arabic language materials can include different materials based on language skills, so as to achieve the objectives of integrated instructional materials science. The integration of materials science in learning Arabic to facilitate the practice of science based disciplines at every department in the Islamic Higher Education.